2023
DOI: 10.1101/2023.06.05.543428
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NEMO reshapes the protein aggregate interface and promotes aggrephagy by co-condensation with p62

Abstract: NEMO is a ubiquitin-binding protein which regulates canonical NF-κB pathway activation in innate immune signaling, cell death regulation and host-pathogen interactions. Here we identified an NF-κB-independent function of NEMO in proteostasis regulation by promoting autophagosomal clearance of protein aggregates. NEMO-deficient cells accumulate misfolded proteins upon proteotoxic stress and are vulnerable to proteostasis challenges. Moreover, a patient with a mutation in the NEMO gene resulting in defective bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…Three studies ( 18 , 19 , 20 ) have recently shown that ubiquitin can stimulate the LLPS transition of purified NEMO in vitro and that mutations that remove the C-terminal ubiquitin-binding domain of NEMO abolish this induced transition. Given our results above indicating that perturbation of the IVD interfered with the ability of NEMO to form higher order structures, we next determined whether IVD mutation affected LLPS of NEMO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies ( 18 , 19 , 20 ) have recently shown that ubiquitin can stimulate the LLPS transition of purified NEMO in vitro and that mutations that remove the C-terminal ubiquitin-binding domain of NEMO abolish this induced transition. Given our results above indicating that perturbation of the IVD interfered with the ability of NEMO to form higher order structures, we next determined whether IVD mutation affected LLPS of NEMO.…”
Section: Resultsmentioning
confidence: 99%
“…( 16 , 17 ) demonstrated that binding of linear ubiquitin leads to a variety of distinct conformational states of NEMO. Finally, three recent reports showed that NEMO undergoes signal-induced liquid-liquid phase separation (LLPS) upon binding ubiquitin ( 18 , 19 , 20 ).…”
mentioning
confidence: 99%